Analisis literasi numerasi matematis peserta didik kelas XI dalam menyelesaikan soal AKM - Kristianti Kristianti; Isnaini Handayani (IKIP Siliwangi, 2023)
This study aims to analyze the mathematical numeracy literacy skills of class XI students in solving Minimum Competency Assessment (AKM) questions on sequences and series material. The method used in this research is descriptive qualitative. The subjects in this study were 3 class XI students at one of the East Jakarta high schools. The indicators of mathematical numeracy literacy in this study consist of 4 components, including: (1) identifying and explaining mathematical concepts; (2) designing and applying mathematical concepts; (3) completion of the calculation results. The instruments in this study were 6 AKM questions on sequences and series materials and interview guide sheets. The results showed that the highest mathematical numeracy literacy indicator was an indicator of completion of calculation results in which of the three subjects on average could calculate correctly according to the concepts used, while the lowest indicator was an indicator that identified and explained mathematical concepts in which students were mathematically literate. low (S3) are less able to identify by writing mathematical symbols and explain the problems given.